INVITRO EVALUATION OF FREE RADICAL SCAVENGING POTENTIAL OF VARIOUS EXTRACTS OF WHOLE PLANT OF Borreria hispida (Linn) - C.D.Shajiselvin; A.Kottai Muthu (International Journal of Pharma and Bio Sciences, 2010)
The objective of this study was to examine the in vitro free radical scavenging potential of various extracts of whole plant of Borreria hispida (Linn). The antioxidant activity was evaluated by DPPH (α,αdiphenyl-β-picrylhydrazyl) radical scavenging activity, Superoxide anion scavenging activity and Iron chelating activity with reference standard Rutin, Quercetin and EDTA respectively. An IC50 value was found that methanolic extract of Borreria hispida is more effective in DPPH radical scavenging activity than that of ethyl acetate and petroleum ether extract. But when compare to the all the three extracts with Rutin (standard), the methanolic extract of the Borreria hispida showed the moderate result. The methanolic extract of Borreria hispida was found to more antioxidant activity in the scavenging superoxide radical activity. The IC50 value of the methanolic extract of Borreria hispida and Quercetin were found to be 65µg/ml and 60µg/ml respectively. The Iron chelating activity of the methanolic extract of Borreria hispida was found to most effective than that of standard EDTA. It is concluded that a whole plant of the methanolic extract of Borreria hispida was found to contain a noticeable amount of total phenols, which play a major role in controlling antioxidants. The results of this study show that the methanolic extract of Borreria hispida can be used as easily accessible source of natural antioxidants and as a possible food supplement or in pharmaceutical industry.